Essential Social Psychology - Edward Arnold; Pennington Donald C (1991)
This book provides a systematic introduction to the key areas and topics in social psychology. Preface, Acknowledgements, Introduction, Socialization I: The Early Years, Socialization II: A Life-Long Process, Attitudes and Attitude Change, Prejudice and Conflict, Social Cognition I: Perception of Ourselves and Others, Social Cognition II: The Attribution Approach, Interpersonal Attraction, Non-Verbal Communication and Interpersonal Behavior, Social Influence, Groups and Group Performance, References, Subject and Author Index.